MTOR-initiated Metabolic Switch and Degeneration in the Retinal Pigment Epithelium - Go, Young-Mi (FASEB J, 2020)
The retinal pigment epithelium (RPE) is a particularly vulnerable tissue to age-dependent degeneration. Over the lifespan, the RPE develops an expanded endo-lysosomal compartment to maintain the high efficiency of phagocytosis and degradation of photoreceptor outer segments (POS) necessary for photoreceptor survival. As the assembly and activation of the mechanistic target of rapamycin complex 1 (mTORC1) occur on the lysosome surface, increased lysosome mass with aging leads to higher mTORC1 activity. The functional consequences of hyperactive mTORC1 in the RPE are unclear. In the current study, we used integrated high resolution metabolomic and genomic approaches to examine mice with RPE-specific deletion of the tuberous sclerosis 1 (Tsc1) gene which encodes an upstream suppressor of mTORC1. Our data show that RPE cells with constitutively high mTORC1 activity were reprogramed to be hyperactive in glucose and lipid metabolism. Lipolysis was suppressed, mitochondrial carnitine shuttle was inhibited, while genes involved in fatty acid (FA) biosynthesis were upregulated. The metabolic changes occurred prior to structural changes of RPE and retinal degeneration. These findings have revealed cellular events and intrinsic mechanisms that contribute to lipid accumulation in the RPE cells during aging and age-related degeneration.